Aspectos do comportamento aerodinâmico de turbinas eólicas de eixo horizontal - Souza, Lucas Teotônio de (2019)
Wind turbines, both in onshore and offshore applications, are exposed to atmospheric boundary layer wind effects. The analytical calculation of the aerodynamic forces acting on the rotor is usually developed on the basis of the classic blade element momentum (BEM) theory, by considering the wind speed constant over time. To evaluate the effects of wind turbulence, it is necessary to perform dynamic analyses of the rotor - tower - foundations coupled system. With this objective this work presents and discusses the results from a study of the structural dynamic behavior of a large onshore horizontal axis wind turbine with the aid of the computational tools FAST and TurbSim, developed by the National Renewable Energy Laboratory, USA. The influence of blade tip losses, as well as the rotor plane yaw and inclination angles are considered in the calculation of the aerodynamic forces applied to the rotor shaft. A number of wind speed field conditions specified by design standards in ultimate limit state (ULS) situations are analyzed and parametric studies of interest are performed, such as the influence of the rotor-tower dynamic coupling, the statistical regularity of the generated wind fields and the contribution of wind forces on the tower to the structure’s response. The maximum responses, obtained by post-processing of data, are calculated by the gust response factor, proposed by Davenport. The study was applied to a 5MW wind turbine model, designed by the cited laboratory.